2021
DOI: 10.1002/jso.26736
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic models predicting non‐sentinel lymph node metastasis in cutaneous melanoma patients: Are they useful for patients with a single positive sentinel node?

Abstract: Background and Objectives Of clinically node‐negative (cN0) cutaneous melanoma patients with sentinel lymph node (SLN) metastasis, between 10% and 30% harbor additional metastases in non‐sentinel lymph nodes (NSLNs). Approximately 80% of SLN‐positive patients have a single positive SLN. Methods To assess whether state‐of‐the‐art clinicopathologic models predicting NSLN metastasis had adequate performance, we studied a single‐institution cohort of 143 patients with cN0 SLN‐positive primary melanoma who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…It suggests that to predict NSN status might still be important in future practice. There have been several studies published to evaluate prognostic factors or establish clinicopathologic models to predict positive NSN [15][16]. In our previous study based on 328 SN positive melanoma in Chinese population, the Breslow thickness, Clark level and number of positive SNs were independently related to positive NSN.…”
Section: Discussionmentioning
confidence: 89%
“…It suggests that to predict NSN status might still be important in future practice. There have been several studies published to evaluate prognostic factors or establish clinicopathologic models to predict positive NSN [15][16]. In our previous study based on 328 SN positive melanoma in Chinese population, the Breslow thickness, Clark level and number of positive SNs were independently related to positive NSN.…”
Section: Discussionmentioning
confidence: 89%
“…It suggests that predicting NSN status might still be important in the future practice. Several studies have been published to evaluate prognostic factors or establish clinicopathologic models to predict positive NSN [ 15 , 16 ]. In our previous study based on 328 SN-positive melanoma in the Chinese population, Breslow thickness, Clark level, and the number of positive SNs were independently related to positive NSN.…”
Section: Discussionmentioning
confidence: 99%
“…Most of them elaborate extensively on clinicopathological features. A recent study performed by a Dutch-American group has shown that currently available predictive models are not efficient and not validated for single positive SLNB, and they show limited performance in this subgroup of patients [25]. Their study analyzed the specific patient group with a single positive SLN, and they did not find any model that would identify patients at high risk of NSLN in a group of single positive SLN.…”
Section: Prognostic and Predictive Toolsmentioning
confidence: 96%
“…For the purpose of analysis, all patients were clustered into three groups according to the type of surgery before adjuvant treatment: surgery without recurrence (primary melanoma and nodes: positive sentinel lymph node biopsy (SLNB) +/− completion lymph node dissection (CLND)), surgery after local recurrence (therapeutic lymph node dissection (TLND) +/− in-transit resection), and surgery after distant recurrence (resected M1) (Table 2). Within the primary surgery group (resection of primary melanoma and/or nodes), there were patients who underwent TLND without SLNB (33,25.4%), those who underwent CLND after positive SLNB (63, 48.5%), and those who had positive SLNB but no CLND afterwards (34,26.2%). There were 174 (70%) patients with intervals longer than 13 weeks from the last operation to adjuvant treatment start.…”
Section: Patient and Tumor Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation